Phyto-Enrichment of Yogurt to Control Hypercholesterolemia: A Functional Approach - Harsh Kumar; Kanchan Bhardwaj; Natália Cruz-Martins; Ruchi Sharma; Shahida Anusha Siddiqui; Daljeet Singh Dhanjal; Reena Singh; Chirag Chopra; Adriana Dantas; Rachna Verma; Noura S. Dosoky; Dinesh Kumar (Molecules, 2022)
Cholesterol is essential for normal human health, but elevations in its serum levels have led to the development of various complications, including hypercholesterolemia (HC). Cholesterol accumulation in blood circulation formsplaques on artery walls and worsens the individuals’ health. To overcome this complication, different pharmacological and non-pharmacological approaches are employed to reduce elevated blood cholesterol levels. Atorvastatin and rosuvastatin are the most commonly used drugs, but their prolonged use leads to several acute side effects. In recent decades, the potential benefit of ingesting yogurt on lipid profile has attracted the interest of researchers and medical professionals worldwide. This review aims to give an overview of the current knowledge about HC and the different therapeutic approaches. It also discusses the health benefits of yogurt consumption and highlights the overlooked phyto-enrichment option to enhance the yogurt’s quality. Finally, clinical studies using different phyto-enriched yogurts for HC management are also reviewed. Yogurt has a rich nutritional value, but its processing degrades the content of minerals, vitamins, and other vital constituents with beneficial health effects. The option of enriching yogurt with phytoconstituents has drawn a lot of attention. Different pre-clinical and clinical studies have provided new insights on their benefits on gut microbiota and human health. Thus, the yogurtphyto-enrichment with stanol and β-glucan have opened new paths in functional food industries and found healthy andeffective alternatives for HC all along with conventional treatment approaches.